TRPV1 Activation Antagonizes High-Fat Diet-Induced Obesity at Thermoneutrality and Enhances UCP-1 Transcription via PRDM-16 - Padmamalini Baskaran; Noah Gustafson; Nicolas Chavez (MDPI AG, 2024)
Body weight is a balance between energy intake and energy expenditure. Energy expenditure is mainly governed by physical activity and adaptive thermogenesis. Adaptive dietary thermogenesis in brown and beige adipose tissue occurs through mitochondrial uncoupling protein (UCP-1). Laboratory mice, when housed at an ambient temperature of 22-24 °C, maintain their body temperature by dietary thermogenesis, eating more food compared to thermoneutrality. Humans remain in the thermoneutral zone (TNZ) without expending extra energy to maintain normal body temperature. TRPV1 activation by capsaicin (CAP) inhibited weight gain in mice housed at ambient temperature by activating UCP-1-dependent adaptive thermogenesis. Hence, we evaluated the effect of CAP feeding on WT and UCP-1−/− mice maintained under thermoneutral conditions. Our research presents novel findings that TRPV1 activation by CAP at thermoneutrality counters obesity in WT mice and promotes PRDM-16-dependent UCP-1 transcription. CAP fails to inhibit weight gain in UCP-1−/− mice housed at thermoneutrality and in adipose tissue-specific PRDM-16−/− mice. In vitro, capsaicin treatment increases UCP-1 transcription in PRDM-16 overexpressing cells. Our data indicate for the first time that TRPV1 activation counters obesity at thermoneutrality permissive for UCP-1 and the enhancement of PRDM-16 is not beneficial in the absence of UCP-1.